STATUS SOSIAL EKONOMI, GAYA, DAN PRESTASI BELAJAR - Roni Priyo Jatmiko (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2017)
This research was try to explain the influence of student’s parents social economic status and student’s learning style to student’s learning achievement, especially at VIIIth Graders Student 2015/2016 Academic Year of SMP Negeri 3 Kecamatan Ponorogo. The subjects were 56 students. Data obtained by questionnaire and documentation mode, for analyst by multiple regression methode, while the hypothesises are tested by using Ftest and Ttest. The result of research indicate that by togetherness, student’s parents social economic status and student’s learning style is own the influence to student’s learning achievement. There are positive values of regression coefficient among student’s parents social economic status and student’s learning with student’s learning achievement. The Ttest values indicate that student’s parents social economic status has and student’s learning style have significance influence to student’s learning achievement.